STRUCTURE AND CONTENT OF PRODUCTION ANALYSIS IN RETAIL CHAINS - A. Dvoryankina; T. Rogulenko (Вестник университета)
The structure and content of business analysis in trade networks are determined. The principle of choosing critical indicators is proposed. The main stages of strategic analysis are determined. The key points of production analysis in retail are considered. The principles of the product range formation are stated. The main indicators for the analysis of human resources indicated. The importance of monitoring the level of labor productivity noted. The list of types of analytical activity of the advertising unit outlined. The issues of analysis in the enterprise security system are touched.